Answer:
B. 3x+5−4x=−(x+8)
Explanation:
3x+5−4x=−(x+8)
Step 1: Simplify both sides of the equation.
3x+5−4x=−(x+8)
3x+5+−4x=−x+−8
(3x+−4x)+(5)=−x−8
−x+5=−x−8
−x+5=−x−8
Step 2: Add x to both sides.
−x+5+x=−x−8+x
5=−8
Step 3: Subtract 5 from both sides.
5−5=−8−5
0=−13
So, there is no solution
Hope this Helps!
Answer: B!
Step-by-step explanation:
This looks like the additive inverse property, because when you add something to its negative counterpart (or its additive inverse), you get 0 as a sum.
Another example would be 2+ (-2) = 0. -2 is the additive inverse for 2.
=(120/48)
=5/2
=(4/2)+(1/2)
=2+(1/2) or 2.5